Objectively measured walkability and active transport and weight-related outcomes in adults: a systematic review - Grasser, Gerlinde; Van Dyck, Delfien; Titze, Sylvia; Stronegger, Willibald (International journal of public health, 2013)
Objectives The aim of this study was to investigate which GIS-based measures of walkability (density, land-use mix, connectivity and walkability indexes) in urban and suburban neighbourhoods are used in research and which of them are consistently associated with walking and cycling for transport, overall active transportation and weight-related measures in adults. Methods A systematic review of English publications using PubMed, Science Direct, Active Living Research Literature Database, the Transportation Research Information Service and reference lists was conducted. The search terms utilised were synonyms for GIS in combination with synonyms for the outcomes. Results Thirty-four publications based on 19 different studies were eligible. Walkability measures such as gross population density, intersection density and walkability indexes most consistently correlated with measures of physical activity for transport. Results on weight-related measures were inconsistent. Conclusions More research is needed to determine whether walkability is an appropriate measure for predicting weight-related measures and overall active transportation. As most of the consistent correlates, gross population density, intersection density and the walkability indexes have the potential to be used in planning and monitoring.